Predominant Use Of Official Languages In The Mass Media In Cameroon: A Tentative Response To The Problem - (:unkn) unknown (My University, 2008)
The integration of African languages in the mass media has been examined since the implantation of these media in the continent. Some parts of Africa (North, West and South) have efficiently understood the necessity of using national languages on their radio, television and in the written press. Meanwhile, this has been given less attention in Central Africa especially Cameroon. Since independence, the Cameroonian linguistic legacy has been exempted from all vital domains of life, including the media, as a result of the acceptance of English and French as official languages. People from within different local communities are still not accustomed to those “imported languages” even when they found themselves as town dwellers. How do communicators relay messages to beneficiaries of their services in such a complex setting? This paper sets out to explore such problems and suggests a number of solutions.
Keywords: African Research